Model of Religious Moderation in Universities: Alternative Solution to Liberal, Literal and Radical Islam - Muhamad Parhan; Risris Hari Nugraha; Mohammad Rindu Fajar Islamy (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The existence has recently significantly disrupted the stability of religious harmony in Indonesia. The current reality of extreme and exclusive religion is spreading in the academic world. Students who only use rational logic without religious texts will be trapped in radical logical reasoning, so they tend to be liberal. On the other hand, students who only adhere to religious texts without being accompanied by critical logic will be dogmatic in understanding religious texts literally. The existence of an understanding of Islam with two camps of liberal and literal interpretation is not in line with a moderation in religion which will obscure the actual value of Islamic teachings. This ideology will produce radical religious perspectives, attitudes, and behaviors. The research approach is research and development, which collaborates quantitative and qualitative. Methods of collecting data through interviews, observation, questionnaires, and documentation. The selection of respondents and informants through random sampling technique, while data analysis using the Miles and Huberman approach. This study aims to offer a model for implementing religious moderation learning in higher education to stem contradictory ideologies with Islamic teachings.